Apologetika Terhadap Higher Criticisim Atas Inerrancy Alkitab Bagi Iman Kristen - Wendy Efriduansyah Situmorang; Miner Gulo; Otomosi Ndururu; Feronika Pasaribu (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2025)
The Bible, God's word, is a major doctrine in the Christian faith. When reading the Bible you must submit to the system of understanding the Bible, reading the Bible then criticizing the Bible is the wrong system or method. Biblical criticism, both textual criticism and historical criticism, began to develop specifically during the enlightenment era. The author provides descriptive research methods and provides an explanation that the Bible has innerancy properties, and is a revelation from God, as well as exegetical studies of the Old and New Testaments provide authentic evidence.